Illumina Sequencing Revealed Soil Microbial Communities in a Chinese Alpine Grassland. Issue 3 (16th March 2019) - Shao, Keqiang; Bai, Chengrong; Cai, Jian; Hu, Yang; Gong, Yi; Chao, Jianying; Dai, Jiangyu; Wang, Yongping; Ba, Tunasheng; Tang, Xiangming; Gao, Guang
Abstract: Soil microbial community is the main driving force for nutrient cycles and energy transformations in the alpine grassland. A limited number of studies have investigated the soil microbial diversity in alpine grassland and its influencing factors. Here, we present the first description of microbial communities inhabiting the soil from the Bayinbuluke alpine grassland, which lies in the middle of the southern slope of the Tianshan Mountains in Xinjiang, China using Illumina amplicon sequencing. In total, we obtained 432, 820 high quality sequences. The results showed that the Shannon index ranged from 4.631 to 6.578, and extremely diverse soil microbial communities with 41 phyla, or groups, were spread out among the 16 soil samples. The communities were dominated by Thaumarchaeota (20.2 ± 15.5%) in the soil of the alpine grassland. The other five most abundant phyla were Chloroflexi (18.1 ± 9.2%), Acidobacteria (13.2 ± 7.5%), Planctomycetes (10.4 ± 3.4%), Proteobacteria (10.2 ± 8.1%), and Actinobacteria (9.4 ± 4.3%). Additionally, the Candidatus Nitrososphaera, Roseiflexus, Blastocatella . Pirellula, Thiobacillus, Sphingomonas, Rubrobacter were the dominant genus among the 16 soil samples. Statistical analyses showed significant spatial variations in the soil microbial community at our field sites, and total organic carbon was the factor most highly correlated with the soil microbial community variance.